2017
DOI: 10.1093/biolre/iox147
|View full text |Cite
|
Sign up to set email alerts
|

Group B streptococcus activates transcriptomic pathways related to premature birth in human extraplacental membranes in vitro†,‡

Abstract: Streptococcus agalactiae (group B streptococcus [GBS]) infection in pregnant women is the leading cause of infectious neonatal morbidity and mortality in the United States. Although inflammation during infection has been associated with preterm birth, the contribution of GBS to preterm birth is less certain. Moreover, the early mechanisms by which GBS interacts with the gestational tissue to affect adverse pregnancy outcomes are poorly understood. We hypothesized that short-term GBS inoculation activates pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
0
17
0
2
Order By: Relevance
“…We anticipate that GBS-mediated alteration of specific inflammatory and immune responses impacts the ability of infected mothers and neonates to appropriately recognize and respond to GBS infection. Changes in the regulation of cell survival, cytoskeleton rearrangements, and cell-cell contacts are likely to influence GBS colonization and invasion of host cells and negatively impact the integrity of infected tissue, which may also contribute to extraplacental membrane weakening as was discussed in a prior study (25). Additionally, GBS-mediated modulation of cellular metabolism, hormone signaling, and angiogenesis could have severe impacts on fetal development, perhaps contributing to outcomes such as miscarriage or stillbirth.…”
Section: Discussionmentioning
confidence: 90%
“…We anticipate that GBS-mediated alteration of specific inflammatory and immune responses impacts the ability of infected mothers and neonates to appropriately recognize and respond to GBS infection. Changes in the regulation of cell survival, cytoskeleton rearrangements, and cell-cell contacts are likely to influence GBS colonization and invasion of host cells and negatively impact the integrity of infected tissue, which may also contribute to extraplacental membrane weakening as was discussed in a prior study (25). Additionally, GBS-mediated modulation of cellular metabolism, hormone signaling, and angiogenesis could have severe impacts on fetal development, perhaps contributing to outcomes such as miscarriage or stillbirth.…”
Section: Discussionmentioning
confidence: 90%
“…The low induction level of GAS contrasts with much higher induction level by GBS in a similarly set-up of infection (33). GBS infection modified the expression of 32, out of these 133 genes, and, furthermore, the most activated genes compared to uninfected tissue are related to cellular response to cytokine stimulus (33). This supports the capacity of the decidua to elicit an immune response.…”
Section: Resultsmentioning
confidence: 81%
“…This expression pattern suggested that either ex vivo decidua is unable to mount an immune response or that GAS infection restrains this response. The low induction level of GAS contrasts with much higher induction level by GBS in a similarly set-up of infection (33). GBS infection modified the expression of 32, out of these 133 genes, and, furthermore, the most activated genes compared to uninfected tissue are related to cellular response to cytokine stimulus (33).…”
Section: Resultsmentioning
confidence: 99%
“…A recent publication from our laboratory showed that GBS inoculation caused a release of molecular effectors of parturition (matrix metalloproteinases and prostaglandin E2) from human FM explant punches in vitro (Park et al, 2018). In addition, pathway analysis of transcriptomic responses showed that pathways related to inflammation and PTB were activated by GBS inoculation (Park et al, 2018). Studies from our laboratory showed that a metabolite of trichloroethylene (TCE), a common environmental contaminant, modifies innate immune response to GBS in FM explants (Boldenow et al, 2015).…”
Section: Fetal Membranes As a Target Of Bacterial Pathogensmentioning
confidence: 96%
“…In women, GBS infection is associated with PTB at less than 32 weeks gestation (Hillier et al, 1991) and with chorioamnionitis, an inflammation of the chorion layer of the FM (Anderson et al, 2007). A recent publication from our laboratory showed that GBS inoculation caused a release of molecular effectors of parturition (matrix metalloproteinases and prostaglandin E2) from human FM explant punches in vitro (Park et al, 2018). In addition, pathway analysis of transcriptomic responses showed that pathways related to inflammation and PTB were activated by GBS inoculation (Park et al, 2018).…”
Section: Fetal Membranes As a Target Of Bacterial Pathogensmentioning
confidence: 99%